Polyelectrolytes Complex-Based Hydrogels Derived from Natural Polymers and Cannabinoids for Applications as Wound Dressing - Rodriguez Gerpe, Paula (2024)
This research work focuses on the development of an environmentally friendly wound dressing using natural polymers. The inclusion of cannabis in these hydrogels stems from its innovative potential in medicine, particularly for wound healing and pain relief. The hydrogels were prepared by a simple methodology using natural polysaccharides, and cannabis extract through electrostatic interactions and crosslinking with sodium tripolyphosphate (TPP). Several tests were carried out to analyze the morphological, physical, thermal, mechanical, barrier, and antimicrobial properties of these hydrogels. Different types of hydrogels were synthesized including chitosan- gum arabic hydrogel (ChiGA), hydrogel loaded with cannabis extract (ChiGACann), hydrogel crosslinked with TPP (ChiGATPP), and ChiGACann crosslinked with TPP (ChiGACannTPP). The impact of both cannabis extract and TPP crosslinking on the properties of chitosan hydrogels was investigated. The significant swelling capacity measured to the hydrogels, with ChiGACann exhibiting a 250–350% in physiological conditions, making them suitable for wound dressing applications due to their exudate absorption capacity. Antimicrobial activity evaluation demonstrated that the hydrogels acted as barriers against different microorganisms, with Gram-positive bacteria being more sensitive than Gram-negative bacteria. Mechanical testing showed improved mechanical properties in the presence of cannabis extract and TPP crosslinking (20–30 kPa of compression modulus). In conclusion, these results highlight the application of ChiGACann hydrogels as promising materials for manufacturing wound dressings.